2021
DOI: 10.21037/apm-20-1927
|View full text |Cite
|
Sign up to set email alerts
|

Elevated high-sensitivity C-reactive protein levels predict poor outcomes among patients with acute cardioembolic stroke

Abstract: Cardioembolic stroke (CES) is a severe subtype of cerebral infarction, accounting for 20% of cerebral infarctions (1). This condition is characterized by high in-hospital mortality rates (27.3%) (2), neurological deficits at hospital discharge, and a high risk of stroke recurrence (26%) (3). However, the prognostic indicators for patients with CES remain unclear. Acute strokes may trigger an inflammatory response, leading to elevated C-reactive protein (CRP) levels ( 4), which may be associated with poor progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Based on the ROC curves, we found that serum sLOX‐1 and Lp‐PLA2 levels have high diagnostic values for predicting long‐term functional outcomes after ACI, and the combination of the serum sLOX‐1 and Lp‐PLA2 can significantly improve the specificity of prediction without scarifying the sensitivity. Serum level of hs‐CRP is another biomarker that has been studied for ACI (Wang et al, 2021 ). However, combining hs‐CRP with sLOX‐1 improved the sensitivity at the expense of specificity, whereas combining hs‐CRP with Lp‐PLA2 did not yield any improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the ROC curves, we found that serum sLOX‐1 and Lp‐PLA2 levels have high diagnostic values for predicting long‐term functional outcomes after ACI, and the combination of the serum sLOX‐1 and Lp‐PLA2 can significantly improve the specificity of prediction without scarifying the sensitivity. Serum level of hs‐CRP is another biomarker that has been studied for ACI (Wang et al, 2021 ). However, combining hs‐CRP with sLOX‐1 improved the sensitivity at the expense of specificity, whereas combining hs‐CRP with Lp‐PLA2 did not yield any improvement.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a randomized controlled study reported that high-dose statins could reduce the level of inflammatory indicators and improve the outcome of ischemic stroke [29]. Elevated high-sensitivity C-reactive protein and inflammatory indicators also predicted poor outcome of stroke [30,31]. However, the effect of inflammatory indicators on BADrelated stroke was unknown.…”
Section: Introductionmentioning
confidence: 99%